2020
DOI: 10.3389/fncel.2020.00249
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Innate Lymphoid Cells Accumulate in the Brain After Hypoxia-Ischemia but Do Not Contribute to the Development of Preterm Brain Injury

Abstract: Background: The immune system of human and mouse neonates is relatively immature. However, innate lymphoid cells (ILCs), commonly divided into the subsets ILC1, ILC2, and ILC3, are already present in the placenta and other fetal compartments and exhibit higher activity than what is seen in adulthood. Recent reports have suggested the potential role of ILCs, especially ILC2s, in spontaneous preterm labor, which is associated with brain damage and subsequent long-term neurodevelopmental deficits. Therefore, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
(121 reference statements)
2
7
0
Order By: Relevance
“…We found that the majority of meningeal immune cells were BAMs, microglia-like cells, and monocytes, whereas other cell populations, such as neutrophils, T cells, B cells, and ILCs, were present in smaller numbers. This is in agreement with previous studies in which all observed cell populations were described in the meninges of mouse embryos (Tanabe and Yamashita 2018;Utz et al 2020), neonatal mouse pups (Albertsson et al 2018;Nazmi et al 2018;Tanabe and Yamashita 2018;Zelco et al 2020), and adult mice (Gadani et al 2017;Mrdjen et al 2018;Van Hove et al 2019). BAMs are newly defined macrophages found in the meninges, choroid plexus, and perivascular spaces of brain vessels, and only a few studies have characterized the meningeal BAM populations at different developmental ages (Mrdjen et al 2018;Van Hove et al 2019;Utz et al 2020).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We found that the majority of meningeal immune cells were BAMs, microglia-like cells, and monocytes, whereas other cell populations, such as neutrophils, T cells, B cells, and ILCs, were present in smaller numbers. This is in agreement with previous studies in which all observed cell populations were described in the meninges of mouse embryos (Tanabe and Yamashita 2018;Utz et al 2020), neonatal mouse pups (Albertsson et al 2018;Nazmi et al 2018;Tanabe and Yamashita 2018;Zelco et al 2020), and adult mice (Gadani et al 2017;Mrdjen et al 2018;Van Hove et al 2019). BAMs are newly defined macrophages found in the meninges, choroid plexus, and perivascular spaces of brain vessels, and only a few studies have characterized the meningeal BAM populations at different developmental ages (Mrdjen et al 2018;Van Hove et al 2019;Utz et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…We identified neutrophils, ILCs, T cells, and B cells in the neonatal mouse meninges, which agreed with previous findings (Albertsson et al 2018;Nazmi et al 2018;Zelco et al 2020). These clusters were much smaller than BAM and microglia-like cell populations and contained only a few hundred cells (Fig.…”
Section: Neutrophils Ilcs T Cells and B Cells Are A Minor Fraction Of The Resident Meningeal Leukocytes In Neonatal Micesupporting
confidence: 93%
See 3 more Smart Citations